2023
DOI: 10.3390/math11020327
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Reinforcement Learning Algorithm for 2D Irregular Packing Problems

Abstract: Packing problems, also known as nesting problems or bin packing problems, are classic and popular NP-hard problems with high computational complexity. Inspired by classic reinforcement learning (RL), we established a mathematical model for two-dimensional (2D) irregular-piece packing combined with characteristics of 2D irregular pieces. An RL algorithm based on Monte Carlo learning (MC), Q-learning, and Sarsa-learning is proposed in this paper to solve a 2D irregular-piece packing problem. Additionally, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Learning irregular packing skills is a much more challenging problem, where the learning model has to recognize the complex object shapes and handle the continuous decision space of object poses. Two recent works [Fang et al 2023;Goyal and Deng 2020] considered packing of irregular shapes. Goyal and Deng [2020] proposed a problem set for 3D packing problems and showed that a neural shape selector trained via reinforcement learning outperforms heuristic baselines.…”
Section: Learned Packing Policymentioning
confidence: 99%
See 3 more Smart Citations
“…Learning irregular packing skills is a much more challenging problem, where the learning model has to recognize the complex object shapes and handle the continuous decision space of object poses. Two recent works [Fang et al 2023;Goyal and Deng 2020] considered packing of irregular shapes. Goyal and Deng [2020] proposed a problem set for 3D packing problems and showed that a neural shape selector trained via reinforcement learning outperforms heuristic baselines.…”
Section: Learned Packing Policymentioning
confidence: 99%
“…Goyal and Deng [2020] proposed a problem set for 3D packing problems and showed that a neural shape selector trained via reinforcement learning outperforms heuristic baselines. Fang et al [2023] also trained a neural shape selector via reinforcement learning. Both algorithms use heuristic rules for the low-level pose computation and Fang et al [2023] even used NFP-based pose computation.…”
Section: Learned Packing Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Xiaofei Xu et al [1] tried to solve the rectangular packing problem by using transfer ant colony reinforcement learning, and with the help of the "trial and error" learning mode, the acquisition and update of the knowledge were completed by using an ant colony with self-learning ability in the knowledge matrix. J Fang et al [37,38] and X Zhao et al [39] used the Monte Carlo (MC) algorithm and Q-learning algorithm in reinforcement learning to solve the sequence optimization problem in 2D irregular piece packing and rectangular packing, respectively, but the search had a certain randomness. The combination of machine learning and intelligent algorithms has also achieved certain achievements in some fields.…”
Section: Introductionmentioning
confidence: 99%